Pelaksanaan Kegiatan Muhadharah Di Pondok Pesantren Subulussalam Palembang - Rama Ardiansyah; Saipul Annur; Maryance Maryance (Universitas Kristen Indonesia Toraja, 2026)
This study aims to analyze the implementation of muhadharah activities at the Subulussalam Islamic Boarding School in Palembang as a means of developing students’ public speaking and da’wah skills. Muhadharah activities are speech or lecture exercises conducted regularly to enhance students’ courage, self-confidence, and communication skills in public settings. This study was motivated by the ongoing challenges in implementing these activities, such as low self-confidence among students and limited supporting facilities and infrastructure. This study employs a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The results indicate that the implementation of the muhadharah activities has proceeded in a structured manner through the stages of preparation, execution, and conclusion, supported by clear organization. However, challenges remain, such as time constraints, limited facilities, and the students’ mental readiness. Efforts made to overcome these obstacles include coaching, providing motivation, adjusting schedules, and making optimal use of available facilities.